Wear behaviour of Ti6Al4V alloy blasted with zirconia/hydroxyapatite powders - Yoruc, A. B. Hazar; Elkoca, O.; Yildiz, Harika Eksioglu; Koyun, Ahmet (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose The purpose of this paper is to investigate the effect of blasting treatment with zirconia/hydroxyapatite powders on the surface roughness, in vitro bioactivity and wear behavior of Ti6Al4V alloy (Grade V). Design/methodology/approach - Ti6Al4V specimens were sandblasted with ZrO2 and HA [Ca-10(PO4)(6)(OH)(2)] powders in a commercial blasting cabinet. Surface analysis was performed evaluating eroded surfaces by scanning electron microscopy. Roughness surface analysis of the samples was performed with a surface roughness tester and in vitro bioactivity of titanium surfaces was examined in the simulated body fluid (SBF) solution before and after blasting. Wear resistance is evaluated by the weight loss during the test. Findings - The highest value of surface roughness is obtained with a mixture of 25 percent ZrO2 + 75 percent HA (Z25). Z25 exhibited also lower weight loss than Ti6Al4V and other treated samples. These results indicate that surface treatment with 25 percent ZrO2 + 75 percent HA provides the highest amount of HA adhesion on the surface of Ti6Al4V implant. Finally, the sample surfaces were contacted with SBF solutions for seven days, and Ca/P accumulation was identified on the blasted surfaces. ZrO2/HA blasting method can be used to improve the wear characteristics and the biocompatibility of the implant materials. Originality/value - The paper provides information about the effect of ZrO2/HA blasting treatment on the surface properties, in vitro bioactivity and wear behavior of Ti6Al4V implant materials.
Keywords: Wear; Surface treatment; ND-YAG LASER; SURFACE; BONE; Engineering